2023
DOI: 10.1186/s12936-022-04414-0
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicles for surveillance and control of vectors of malaria and other vector-borne diseases

Abstract: The use of Unmanned Aerial Vehicles (UAVs) has expanded rapidly in ecological conservation and agriculture, with a growing literature describing their potential applications in global health efforts including vector control. Vector-borne diseases carry severe public health and economic impacts to over half of the global population yet conventional approaches to the surveillance and treatment of vector habitats is typically laborious and slow. The high mobility of UAVs allows them to reach remote areas that mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 89 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…For example, in case of population suppression gene drive, reductions in the densities of target populations might lead to reductions in the densities of predators or increases in in the densities of non-target competitor species [ 23 ]. Here, sampling and detection of eDNA from in aquatic habitats, in combination with quantitative PCR methods [ 115 , 116 ], could be used to assess the abundance of such species of mosquito target populations, potential in conjunction with UAV technology [ 106 , 107 , 117 ].…”
Section: Assessing Genetic Efficacy In Phase 2amentioning
confidence: 99%
“…For example, in case of population suppression gene drive, reductions in the densities of target populations might lead to reductions in the densities of predators or increases in in the densities of non-target competitor species [ 23 ]. Here, sampling and detection of eDNA from in aquatic habitats, in combination with quantitative PCR methods [ 115 , 116 ], could be used to assess the abundance of such species of mosquito target populations, potential in conjunction with UAV technology [ 106 , 107 , 117 ].…”
Section: Assessing Genetic Efficacy In Phase 2amentioning
confidence: 99%
“…It is necessary to consider the meteorological conditions for the best drone performance and the characteristics of the terrain and to avoid electromagnetic interference that could put the activity at risk. The multirotor drone system is the best option for areas with high tree vegetation coverage or urban areas with many obstacles because it takes off and lands from very small spaces [39]. Flight altitude needs to be carefully determined, taking into account the type of sensor to be used, the data analysis goals, the level of scene complexity, and legal requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Using RGB and NDVI orthophotographs, it was found that the best flight altitude to identify tolares of Parastrephia lepidophilla and Distichia muscoides was 25 m, followed by 50 m [40]. Studies using drones to monitor mosquito-breeding sites tend to fly at 50 to 100 m [17,21,39]. For our study, the resolution obtained for the MicaSense ® camera used was 0.07 m/pixel at an altitude of 100 m; at this spatial resolution, the smallest elements of the Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Unmanned aerial vehicles (UAVs) have gained significant importance in recent decades in military, commercial, and civilian applications, such as reconnaissance, target engagement, combat support, traffic and border control, aerial surveillance, law enforcement, remote parcel delivery, hidden and hazardous area exploration, onset detection of subpavement voids, maintenance and repair of aircraft, crop spraying, wildfire fighting, search and rescue operations, climate change monitoring, etc. [1][2][3][4][5][6]. Part of the success of these vehicles is commonly due to their (i) low prices, (ii) low cost utility, (iii) low maintenance, (iv) faster deployment, (v) easier, efficient, and practical operation compared with conventional manned aircraft and road delivery vehicles, (vi) large capacity to take closer footage without compromising the quality of both photos and video, (vii) reduction of pilot fatality and injury rates mid-flights, (viii) ability to land or take off without having to use runways, etc.…”
Section: Introductionmentioning
confidence: 99%